Impact of Microcredit on Living Standard of Dairy Entrepreneurs: Special Focus on Oddusuddan DS Division in Mullaitivu District - Balagobei, Saseela; Aravinthakumar, Sankeetha (Indian Journal of Finance and Banking, 2019)
Microcredit is part of micro finance, which provides a wider range of financial services for low income people. Micro credit serves as a vital role for Living standard of poor people in the developing countries as well as in Sri Lanka. In this Study Oddusuddan DS division in Mullaitivu district was selected as research area. After the 30 years conflict situation most people in the Oddusuddan area in Mullaitivu district are subordinate to the poverty line, because most of the displaced people who are female other than male staying here. Women lost their male relatives in struggle, and forced to take a responsibility of their family in order to look after their children, aged parents and their male relatives. Micro credit helps the poor people particularly women in effective ways in order to create income generating activities. The prime objective of this study is to investigate the impact of Microcredit on living standard of dairy entrepreneurs in Oddusuddan DS division in Mullaitivu District. In the rural areas of Mullaitivu, Oddusuddan Divisional Secretariat Divisions 100 dairy entrepreneurs were selected as the sample size of population. The selected entrepreneurs who have received loan from samurdhi bank for dairy farming activities in Oddusuddan DS Division. Primary data were used for gathering information and quantitative analysis was carried out to find out the results. In the quantitative analysis the correlation and regression methods were employed to examine the hypotheses by using SPSS. The result of this study concluded that there is a positive impact of samurdhi micro credit on living standard of dairy entrepreneurs in Oddusuddan DS Division. In addition to this, using micro credit facilities create more job opportunities and variety of economic activities and improve household education, income, saving and heath condition of the people. The study recommends that micro credit institution should consider improve the living standard of dairy entrepreneurs through increase the loan amount with lower interest rate.